Rearward visibility assessment and a proposed performance scoring for ASEAN NCAP - Abd Rahman, Badruzzaman; Mohd Sohimin, Muhammad H F; Meor Said, Mior A; Tuan Kamaruddin, Tengku Nordayana Akma; Abu Husain, Nurulakmar; Mohamad Jamil, Siti Nurnadilla; Balaka, Ridway; Abu Kassim, Khairil A (2019)
Asia has the highest number of registered motorcycles globally and the recent data has shown that motorcycles fatalities has been the major accident and death cases in ASEAN Region. One of the major concerns is the visibility of motorcycles to other vehicles on the road. Thus, in this project, ECE R46 and FMVSS regulations have been referred as the base guidelines to establish a novel test protocols for vehicles rearward visibility assessment. Sixteen cars have been benchmarked and analysed in term of their rear-view mirror (Class I) and external mirror (Class III) performance. Motorcycles visibility to the vehicles’ Class I and Class III mirrors also been assessed by converting the measured data into number of motorcycles based on its width. A proposed performance scoring system for ASEAN NCAP has been developed based on that to address the Motorcycle Safety pillar.